EFFECT OF CONSUMER PERCEIVED INTRUSIVENESS ON PURCHASE INTENTION: THE CASE OF YOUTUBE VIDEO ADS FOR MILLENNIALS IN PONTIANAK - Geovani, Andre B1024151001 (Jurnal Manajemen Update, 2019)
ABSTRACTThe purpose of this research is to analyze the relationship of Consumer Perceived Intrusiveness on Shopee YouTube video ads to their Purchase Intention in case of Millennials in Pontianak. The research has been conducted by using Advertisement Attitude and Brand Attitude as other variables because it is naturally stimulated as consumer exposed to the video ad. These days, the marketing strategy often uses a YouTube video ad as one of main tools in order to get attention from consumer.. There have been huge increase in encouragement across the world to online advertising as customers are shifting form using TV to Internet (especially YouTube). This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire consist of sample which is obtained through distribution to 120 respondents in 4 different groups who fulfill the requirements. The sample of this research is Millennials in Pontianak who are in age of 18 to 37 years old and have ever bought product from Shopee for the last six months. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypotheses of the research are (H1a, H1b, H1c, and H1d): Consumer Perceived Intrusiveness have a negative effect on Advertisement Attitude in YouTube video ads; (H2a, H2b, H2c, and H2d): Consumer Advertisement Attitude have a positive effect on Brand Attitude in YouTube video ads; (H3a, H3b, H3c, and H3d): Consumer Brand Attitude have a positive effect on Purchase Intention in YouTube video ads. The result of this research shows that H1b, H1c, H1d, H2a, H2b, H2c, H2d, H3a, H3b, H3c, and H3d are accepted but H1a is rejected.Â Keywords: perceived intrusiveness, advertisement attitude, brand attitude, purchase intention, YouTube video ads.REFERENCEÂ Adobe. (2012, April). Adobe Digital Video Advertising Report. Retrieved from Adobe: http://www.blogs.adobe.com/primetime/files/2013/ll/Monetization-Report_FINALl.pdfAghazadeh, H., & Esfidani, M. R. (2007). Internet Marketing Strategies. Iranian Economic Review, 180-191.Akamai. (2013, October 22). Akamai Data Leveraged in Landmark Scientific Study on the Effectiveness of Online Video Advertisements. Retrieved from Akamai: https://www.akamai.com/us/en/about/news/press/2013-press/akamai-data-leveraged-inlandmark-scientific-study.jspAlijani, G. S., Mancuso, L. C., Kwun, O., & Omar, A. (2010). Effectiveness of Online Advertisement Factors in Recalling a Product. Academy of Marketing Studies Journal.Anderson, M. (2017, July). Why Millennials Donâ€™t Deserve the Bad Rap They Get . Retrieved from Think With Google: https://www.thinkwithgoogle.com/consumer-insights/millennials-youtube-consumer-insights-marketing/Aslam, S. (2018, February 5). YouTube by the Numbers: Stats, Demographics & Fun Facts. Retrieved from Omnicore Agency: https://www.omnicoreagency.com/youtube-statistics/Baker, W., Hutchinson, J. W., Moore, D., & Nedungadi, P. (1986). Brand Familiarity and Advertising: Effects on the Evoked Set and Brand Preference. Advances in Consumer Research, 637-642.Barton, C., Koslow, L., & Beauchamp, C. (2014, January 15). How Millenials Are Changing the Face of Marketing Forever. Retrieved from BCG: https://www.bcg.com/publications/2014/marketing-center-consumer-customer-insight-how-millennials-changing-marketing-forever.aspxBauer, R. A., & Greyser, S. (1968). Advertising in America: The Consumer View. Boston, MA: Harvard University.Beauvillain, A., & Tiger, O. (2013). Perceived Intrusiveness and Trust in Realtion to Online Advertising. UmeÃ¥, Sweden: UmeÃ¥ School of Business and Economics.Biel, A. L., & Bridgwater, C. A. (1990). Attributes of Likable Television Commercials. Journal of Advertising Research, 38-44.Biswas, A., Olsen, J. E., & Carlet, V. (1992). A Comparison of Print Advertisements from the United States and France. Journal of Advertising, 73-81.Â Bowman, M. (2017, February 3). Video Marketing: The Future of Content Marketing. Retrieved from Forbes: https://www.forbes.com/sites/forbesagencycouncil/2017/02/03/video-marketing-the-future-of-content-marketing/#53d936626b53Brackett, L. K., & Carr, B. N. (2001). Cyberspace Advertising vs. Other Media: Consumer vs. Mature Student Attitudes. Journal of Advertising Research, 23-32.Brown, S. (2016). Marketing to Millennials: Improving Relationships with Millennial Consumers Through Online Advertising and Social Media Networking.Brown, S. P., & Stayman, D. M. (1992). Antecedents and Consequences of Attitude toward the Ad: a Meta-analysis. Journal of Consumer Research, 34-51.Campbell, D. T., & Fiske, D. W. (1959). Convergent and Discriminant Validation by the Multitrait-Multimethod Matrix. Psychological Bulletin, 56, 81-105.Carlson, E. (2008). The Lucky Few: Between the Greatest Generation and the Baby Boom. Springer.Carter, L. K., & Emerson, T. L. (2012). In-Class vs. Online Experiments: Is There a Difference? The Journal of Economic Education, 4-18.Chowdhury, H. K., Parvin, N., Weitenberner, C., & Becker, M. (2010). Consumer Attitude toward Mobile Advertising in an Emerging Market: An Empirical Study. Marketing, 206-216.Chungviwatanant, T., Prasongsukarn, K., & Chungviwatanant, S. (2016). A Study of Factors that Affect Consumer's Attitude toward a "Skippable In-stream Ad" on YouTube. AU-GSB e-Journal.Clee, M. A., & Wicklund, R. A. (1980). Consumer Behavior and Psychological Reactance. Journal of Consumer Research, 389.Corley, J. K., Jourdan, Z., & Ingram, W. R. (2013). Internet marketing: a content analysis of the research. Electronic Markets.Dafler, F. (2013, April 23). Terindah. Retrieved from Memahami dan Mempelajari SmartPLS: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlDehkordi, G. J., Rezvani, S., Rahman, M. S., Fouladivanda, F., Nahid, N., & Jouya, S. F. (2012). A Conceptual Study on E-marketing and Its Operation on Firm's Promotion and Understanding Customer's Response. International Journal of Business and Management.Derbaix, C. M. (1995). The Impact of Affective Reactions on Attitudes toward the Advertisement and the Brand: A Step toward Ecological Validity. Journal of Marketing Research, 470-479.Deshwal, P. (2016). Online Advertising and Its Impact on Consumer Behavior. International Journal of Applied Research, 200-204.Ducoffe, R. H. (1996). Advertising Value and Advertising on the Web. Journal of Advertising Research, 21-35.Edwards, S. M., Li, H., & Lee, J.-H. (2002). Forced Exposure and Psychological Reactance: Antecedents and Consequences of the Perceived Intrusiveness Pop-up Ads. Journal of Advertising, 83-95.Fernandez, K. V., & Rosen, D. L. (2000). The Effectiveness of Information and Color in Yellow Pages Advertising. Journal of Advertising, 61-73.Fink, A. (2013). How to Conduct Surveys. A Step-by-Step Guide. Thousand Oak, CA: Sage Publications, Inc.Forno, S. (2017, June 5). YouTube Pre-Roll Ad Length: Timing is Everything. Retrieved from Idea Rocket: https://idearocketanimation.com/15369-pre-roll-ad-length/Fricker, R. D. (2008). Sampling Methods for Web and E-mail Surveys. In N. Fielding, R. Lee, & G. Blank, The Sage Handbook of Online Research Methods (pp. 195-216). Thousand Oaks, CA: Sage Publications, Inc.Ganot, R. (2017, July 25). 8 Types of Online Advertising You Need to Know. Retrieved from Perion: https://www.perion.com/blog/8-types-online-advertising-need-know/Ghozali, I. (2008). Structural Equation Modelling, Edisi II. Semarang: Universitas Diponegoro.Goodrich, K., Schiller, S., & Galletta, D. (2015). Consumer Reactions to Intrusiveness of Online-Video Advertisements: Do Length, Informativeness, and Humor Help (or Hinder) Marketing Outcomes. Journal of Advertising Research.Google. (2019). Ad Placement and How to Create It. Retrieved from Google: https://support.google.com/adsense/answer/160534?hl=enHa, L. (1996). Advertising Clutter in Consumer Magazines: Dimensions and Effects. Journal of Advertising Research, 76-83.Handayani, T. A., & Hudrasyah, H. (2015). Comparative Analysis of Skippable and Non Skippable Pre Roll Advertising on Youtube in Bandung. Journal of Business and Management, 694-701.Hatch, C. (2018). Be in the Know: 2018 Social Media Statistics You Should Know. Retrieved from Disruptive Advertising: https://www.disruptiveadvertising.com/social-media/be-in-the-know-2018-social-media-statistics-you-should-know/Heffner, C. L. (2016). Test Validity and Reliability. Retrieved from AllPsych: http://allpsych.com/researchmethods/validityreliability/Hegner, S. M., Kusse, D. C., & Pruyn, A. T. (2014). Watch It! The Influence of Forced Pre-roll Video Ads Influence on Consumer Persception. Advances in Advertising Research (Vol. VI).Henry. (2011, August 24). Path Analysis with LISREL (Chapter 1). Retrieved from Teori Online: https://teorionline.wordpress.com/2011/08/24/path-analysis-with-lisrel-chapter-1/Holland, M. (2016). How YouTube Developed into a Successful Platform for User-Generated Content. Elon Journal of Undergraduate Research in Communications, 52-59.Hox, J. J., & Bechger, T. (2011). An Introduction to Structural Equation Modeling. Family Science Review, 354-373.Huarng, K.-H., Yu, T. H.-K., & Huang, J. J. (2010). The Impact of Instructional Video Advertising on Customer Purchasing Intentions on the Internet. Service Business, 27-36.HubSpot. (2018). The Ultimate List of Marketing Statistics for 2018. Retrieved from HubSpot: https://www.hubspot.com/marketing-statisticsInteractive Advertising Bureau. (2015). Digital Video In-stream Ad Format Guidelines. Retrieved from Interactive Advertising Bureau: http://www.iab.com/wpcontent/uploads/2015/10/IAB_Digital_Video_Ad_Format_Guidelines_Draft_Public_Comment_091615.pdfInternet Live Stats. (2018). Internet Users. Retrieved from Internet Live Stats: http://www.internetlivestats.com/internet-users/Internet World Stats. (2018). Internet Users. Retrieved from Internet World Stats: https://www.internetworldstats.com/emarketing.htmKamins, M. A., Marks, L., & Skinner, D. (1991). Television Commercial Evaluation in the Context of Program Induced Mood: Congruency versus Consistency Effects. Journal of Advertising, 1-14.Kapferer, J. N. (2004). The New Strategic Brand Management: Creating and Sustaining Brand Equity Long Term. London: Kogan Page.Kaplan, A. M., & Haenlein, M. (2010). Users of the World, Unite! The Challenges and Opportunities of Social Media. Business Horizons, 59-68.Kim, Y. J., & Han, J. Y. (2014). Why Smartphone Advertising Attracts Customers: A Model of Web Advertising, Flow, and Personalization. Computers in Human Behavior, 259-269.Komariah, A., & Satori, D. (2010). Metodologi Penelitian Kualitatif. Bandung: Alfabeta.Korgaonkar, P., & Wolin, L. D. (2002). Web Usage, Advertising, and Shopping: Relationship Patterns. Internet Research, 191-204.Kotler, P., & Keller, K. L. (2012). Marketing Management. 14th Edition. London: Pearson.Krishnan, S. S., & Sitaraman, R. K. (2013). Understanding the Effectiveness of Video Ads: A Measurement Study. Internet Measurement Conference (pp. 149-162). New York: ACM.Kuchler, H. (2015, July 20). YouTube Advertisers Increase 40% in Year. Retrieved from Financial Times: https://www.ft.com/content/470a7c0a-2be8-11e5-8613-e7aedbb7bdb7Lee, E. B., Lee, S. G., & Yang, C. G. (2017). The Influences of Advertisement Attitude and Brand Attitude on Purchase Intention of Smartphone Advertising. Industrial Management & Data Systems, 1011-1036.Leedy, P. D., & Ormrod, J. E. (2001). Practical Research: Planning and Design. London: Pearson.Li, H., & Lo, H. (2015). Do You Recognize Its Brand? The Effectiveness of Online In-stream Video Advertisements. Journal of Advertising.Li, H., Edwards, S. M., & Lee, J.-H. (2002). Measuring the Intrusiveness of Advertisements: Scale Development and Validation. Journal of Advertising, 37-47.Liu, M. T., Huang, Y.-Y., & Minghua, J. (2007). Relations among Attractiveness of Endorsers, Match-up, and Purchase Intention in Sport Marketing in China. Journal of Consumer Marketing, 358-365.Logan, K. (2013). And Now a Word from Our Sponsor: Do Consumers Perceive Advertising on Traditional Television and Online Streaming Video Differently? Journal of Marketing Communications, 258-276.Luscombe, B. (2015, August 27). Meet YouTube's View Master. Retrieved from Time: http://time.com/4012832/meet-youtubes-view-master/Lutz, R. J., MacKenzie, S. B., & Belch, G. E. (1983). Attitude toward the ad as a Mediator of Advertising Effectiveness: Determinants and Consequences. Advances in Consumer Research, 532-539.MacKenzie, S. B., & Lutz, R. J. (1989). An Empirical Examination of the Structural Antecedents of Attitude toward the Ad in an Advertising Pretesting Context. The Journal of Marketing, 48-65.Malhotra, N. K. (2010). Marketing Research: An Applied Orientation (6th Edition). Upper Saddle River, New Jersey: Pearson Prentice Hall.Malhotra, N. K. (2013). Basic Marketing Research: Pearson New International Edition. Harlow: Pearson Education Limited.Maljaars, S. (2016, July). Advertising in Video-on Demand Services, Intrusive and Irritating? Investigating the Effects of In-stream Video Advertisements on Consumersâ€™ Feelings, Cognitions, Attitudes, and Behaviors. Rotterdam: Erasmus School of History, Culture, and Communication.Maurya, U. K., & Mishra, P. (2012). What is a Brand? A Perspective on Brand Meaning. European Journal of Business and Management.McCay-Peet, L., & Quan-Haase, A. (2017). What is Social Media and What Questions Can Social Media Research Help Us Answer? In L. Sloan, & A. Quan-Haase, The SAGE Handbook of Social Media Research Methods (Eds). SAGE Publications.McCoy, S., Everard, A., Polak, P., & Galletta, D. F. (2008). An experimental study of antecedents and consequences of online ad intrusiveness. Journal of Human Computer Interaction, 672-699.McLeod, B. (2018, February 27). How Much Does It Cost to Advertise on Youtube in 2018? Retrieved from Blue Corona: https://www.bluecorona.com/blog/how-much-does-it-cost-to-advertise-youtubeMerriam-Webster. (2018). Merriam-Webster: Questionnaire. Retrieved from Merriam-Webster:: https://www.merriam-webster.com/dictionary/questionnaireMiller, M. (2011). YouTube for Business: Online Video Marketing for Any Business (2nd Edition). Indianapolis: Que Publishing.Mitchell, A. A., & Olson, J. C. (1981). Are Product Attribute Beliefs the Only Mediator of Advertising Effects on Brand Attitude: A Second Look. Journal of Marketing Research, 109-219.Morimoto, M., & Chang, S. (2006). Consumersâ€™ Attitudes Toward Unsolicited Commercial E-mail and Postal Direct Mail Marketing Methods: Intrusiveness, Perceived Loss of Control, and Irritation. Journal of Interractive Advertising, 8-20.Morrison, D. G. (1979). Purchase Intentions and Purchase Behavior. Journal of Marketing, 65-74.Najmi, M., Atefi, Y., & Mirbagheri, S. A. (2012). Attitude toward Brand: An Integrative Look at Mediators and Moderators. Academy of Marketing Studies Journal, 111-133.Newstead, K., & Romaniuk, J. (2010). Cost per Second: The Relative Effectiveness of 15- and 30- Second Television Advertisements. Journal of Advertising Research, 68-76.Pasadeos, Y. (1990). Perceived Informativeness of and Irritation with Local Advertising. Journalism & Mass Communication Quarterly, 35-39.Pashkevich, M., Dorai-raj, S., Kellar, M., & Zigmond, D. (2012). Empowering Online Advertisements by Empowering Viewers with The Right to Choose: The Relative Effectiveness of Skippable Video Advertisement on Youtube. Journal of Advertising Research, 451-457.Patel, N. (2017). How to Use YouTube Ads to Grow Your Business. Retrieved from Neil Patel: https://neilpatel.com/blog/how-to-use-youtube-ads-to-grow-your-business/Petrecca, L. (2006, July 5). Five-second Ads Try to Counter TiVo. Retrieved from USA Today: https://usatoday30.usatoday.com/money/advertising/2006-07-05-5-second-ads-usat_x.htmPhelps, J. E., & Hoy, M. G. (1996). The Aadâ€Abâ€PI Relationship in Children: The Impact of Brand Fmiliarity and Measurement Timing. Psychology & Marketing.RejÃ³n-Guardia, F., & MartÃnez-LÃ³pez, F. J. (2014). Online Advertising Intrusiveness and Consumersâ€™ Avoidance Behavior. In F. L. MartÃnez-LÃ³pez, Handbook of Strategic E-Business Management (pp. 565-586). New York: Springer.Richsen, H. (2015). Validity. Retrieved from Linguistic: http://linguistics.byu.edu/faculty/henrichsenl/ResearchMethods/RM_2_18.htmlRidwan. (2004). Metode dan Teknik Menyusun Tesis. Bandung: Alfabeta.Roscoe, J. (1975). Fundamental Research Statistics for the Behavioral Sciences (2nd Edition). New York: Holt, Rinehart and Winston.Rosenberg, J. M. (1995). Dictionary of Marketing and Advertising (Business Dictionary Series). New York: John Wiley.Sallam, M. A., & Algammash, F. A. (2016). The Effect of Attitude toward Advertisement on Attitude toward Brand and Purchase Intention. International Journal of Economics, Commerce and Management.Saputra, T. S., & Fachira, I. (2014). User's Attitude towards Skippable Ads on YouTube TrueView In-Stream - An Empirical Study among College Students in Bandung. Journal of Business and Management, 850-859.Schmidt, S., & Eisend, M. (2015). Advertising Repetition: A Meta-analysis on Effective Frequency in Advertising. Journal of Advertising, 415-428.Schrage, M. (1994). Let's Make A Deal. Advertising Age.Sekaran, U., & Bougie, R. (2016). Research Methods For Business: A Skill Building Approach, 7th Edition. Chichester, West Sussex, United Kingdom: John Wiley & Sons.Shadish, W. R., Cook, T. D., & Campbell, D. T. (2002). Experimental and Quasi-Experimental Designs for Generalized Causal Inference. Boston, MA: Houghton Mifflin.Shavitt, S., Lowrey, P., & Haefner, J. (1998). Public Attitudes toward Advertising: More Favorable Than You Might Think. Journal of Advertising Research, 363-382.Silva, M. G. (2013). The Impact of YouTube Brand's Channels on Brand Related Attitudes: Affective Commitment, Affective Brand, Loyalty and Purchase Intention. Master of Science in Marketing Thesis.Spears, N., & Singh, S. N. (2004). Measuring Attitude toward the Brand and Purchase Intention. Journal of Current Issues & Research in Advertising, 53-66.Speck, P. S., & Elliot, M. T. (1997). Predictors of Advertising Avoidance in Print and Broadcast Media. Journal of Advertising, 61-76.Statista. (2019). Number of YouTube Users Worldwide from 2016 to 2021. Retrieved from Statista: https://www.statista.com/statistics/805656/number-youtube-viewers-worldwide/Sulaksana, U. (2007). Integrated Marketing Communications: Teks dan Kasus. Yogyakarta: Pustaka Pelajar.Sumedi, B. P. (2016). Using Likert Type Data in Social Science Research: Confussion, Issues and Challenges. International Journal of Contemporary Applied Sciences, 36-49.Tavor, T. (2011). Online Advertising Development and Their Economic Effectiveness. Australian Journal of Business and Management Research, 121-133.Techopedia. (2018). Online Advertising. Retrieved from Techopedia: https://www.techopedia.com/definition/26362/online-advertisingTechTarget. (2018). Definition: Hypothesis. Retrieved from TechTarget: https://whatis.techtarget.com/definition/hypothesisTerkan, R. (2014). Importance of Creative Advertising and Marketing According to University Students' Perspective. International Review of Management and Marketing, 239-246.Ting, H., & de Run, E. C. (2015). Attitude toward Advertising: A Young Generation Cohort's Perspective . Asian Journal of Business Research.Truong, Y., & Simmons, G. (2010). Perceived Intrusiveness in Digital Advertising: Strategic Marketing Implications. Journal of Strategic Marketing, 239-256.Walker, H. M. (1931). Studies in the History of the Statistical Method. Baltimore, MD: William & Wilkins Co.Wang, J., & Calder, B. J. (2006). Media Transportation and Advertising. Journal of Consumer Research, 151-162.Wardani, P. (2012). Faktor-faktor yang Mempengaruhi Luas Pengungkapan Sukarela. Surabaya: Fakultas Bisnis Universitas Katolik Widya Mandala.Wikipedia. (2015). Convergent Validity. Retrieved from Wikipedia: https://en.wikipedia.org/wiki/Convergent_validityWikipedia. (2016). Wikipedia. Retrieved from Discriminant Validity: https://en.wikipedia.org/wiki/Discriminant_validityWilliams, C. (2007). Research Methods. Journal of Business & Economics Research.Ying, L., Korneliussen, T., & Grohaug, K. (2009). The Effect of Ad Value, Ad Placement and Ad Execution on the Perceived Intrusiveness of Web Advertisements. International Journal of Advertising, 623-638.YouTube. (2019). How Video Ads Work. Retrieved from Google Support: https://support.google.com/displayspecs/answer/6244557?hl=en&ref_topic=6244532YouTube. (2019). YouTube Advertising Formats. Retrieved from Google Support: https://support.google.com/youtube/answer/2467968?hl=enZaitceva, E. (2018). The Fight for Customer's Attention: YouTube as an Advertising Platform. Bachelors' Thesis Degree Program in International Business University of Applied Science.Zanot, E. (1984). Public Attitude toward Advertising: The American Experience. International Journal of Advertising, 3-15.Â Â Â